2017
DOI: 10.4103/1735-5362.207203
|View full text |Cite
|
Sign up to set email alerts
|

Development of dry powder inhaler containing tadalafil-loaded PLGA nanoparticles

Abstract: Inhalable dry powders containing poly lactic-co-glycolic acid (PLGA) nanoparticles (NPs) were developed for the delivery of tadalafil (TAD) for treatment of life-treating pulmonary arterial hypertension. Taguchi design was employed to evaluate the effects of different formulation variables on the physicochemical characteristics of PLGA-NPs prepared using emulsion solvent evaporation method. Inhalable PLGA-NPs of TAD were successfully prepared by co-spray drying the PLGA-NPs with inert carriers. Physicochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…2.4 Preparation of poly lactic-co-glycolic acid (PLGA) nanoparticles loaded with tadala l Tadala l loading NPs were kindly provided by the National Research Center (NRC), Cairo, Egypt. Tadala lloaded NPs were prepared according to the solid-in-oil-in-water (s/o/w) emulsion technique [12]. PLGA (35 mg) was dissolved in dichloro-methane for 6 h to obtain a uniform PLGA solution.…”
Section: Preparation Of Chitosan (Cs) /Alginate (Alg) Nanoparticles L...mentioning
confidence: 99%
“…2.4 Preparation of poly lactic-co-glycolic acid (PLGA) nanoparticles loaded with tadala l Tadala l loading NPs were kindly provided by the National Research Center (NRC), Cairo, Egypt. Tadala lloaded NPs were prepared according to the solid-in-oil-in-water (s/o/w) emulsion technique [12]. PLGA (35 mg) was dissolved in dichloro-methane for 6 h to obtain a uniform PLGA solution.…”
Section: Preparation Of Chitosan (Cs) /Alginate (Alg) Nanoparticles L...mentioning
confidence: 99%
“…Prostacyclin (PGI 2 ) analogue [27,28,29,30], PDE5 inhibitors [31,32], ERA [33], oligonucleotides [34,35], pitavastatin [36,37], imatinib [38], rapamycin [39], and fasudil [40]-loaded NPs have been reported to be effective in animal PAH models and in vitro studies (Table 1). All of the data in the studies were obtained in animal models of PAH or in vitro studies and have not yet been translated to human trials.…”
Section: Nano-dds For Pah Treatmentmentioning
confidence: 99%
“…On this basis, the current work endeavors for the first time-to the best of our knowledge-to develop TD-NEs that can resist aqueous dilution to be used for the treatment of pediatric PAH via nebulization using a jet nebulizer. Nanoparticles, microspheres, and nanocomposites of TD have been previously developed as inhalable dry powders for treating PAH [26][27][28]. However, it has been reported that dry powder formulations encounter problems during powder processing and re-dispersion (adhesion and strong agglomeration), which makes them unsuitable for efficient inhalation [10].…”
Section: Introductionmentioning
confidence: 99%